Prinsip-Prinsip Praktis Bersikap dalam Mendampingi Orang Dewasa Belajar - Dwi Ariefin (Didache: Journal of Christian Education, 2023)
With the special conditions of adults, teaching them needs to be based on appropriate practical principles. Although not the dominant determinant, educators still need to master it properly to be successful in accompanying adults in learning. Therefore it is necessary to study practical principles for the teacher in teaching adults. Through a literature review, an analysis and synthesis of previous findings has been carried out. At least there are six affective principles that need to be considered, namely recognizing them as adults, paying attention to their experiences, understanding their needs, understanding their goals, strengthening their motivation, appreciating the uniqueness of each individual, and giving roles in the main group. Teachers manage adult study groups keeping in mind their independent, personal and experienced features. If the practical principles of the application will increase the effectiveness of interpersonal relationships that respect each other and a conducive adult learning atmosphere.